Endogenous endophthalmitis due to Serratia marcescens secondary to late‐onset empyema Post‐Cardiac surgery in an End‐Stage renal disease patient on peritoneal dialysis - Sreethish Sasi; Hazem Faraj; Raja Barazi; Jouhar Kolleri; P. Chitrambika; Muna A. Rahman Al Maslamani; Maisa Ali (Clinical Case Reports, 2023)
Abstract Endogenous bacterial endophthalmitis results from bacterial seeding of the eye during bacteremia. A diagnosis of endogenous bacterial endophthalmitis requires clinical findings such as vitritis or hypopyon along with positive blood cultures. Serratia marcescens is the second most common pathogen causing hospital‐acquired ocular infections. This report describes a case of endogenous bacterial endophthalmitis caused by S. marcescens in an older adult with end‐stage renal disease (ESRD) on peritoneal dialysis, who had late‐onset pleural empyema secondary to coronary artery bypass grafting (CABG). A 61‐year‐old gentleman presented with a two‐day history of cloudy vision, black floaters, pain, swelling, and gradual vision loss in his right eye. There was no history of trauma, ocular surgeries, or previous similar episodes. He had myocardial infarction treated with CABG 3 months back. Examination showed a 3 mm hypopyon in the anterior chamber. He had classic signs of endophthalmitis with positive blood cultures for S. marcescens. He was treated with high‐dose intravenous meropenem and intravitreal ceftazidime without vitrectomy. Endophthalmitis progressed to complete vision loss in his right eye, requiring evisceration. Endophthalmitis caused by S. marcescens is rare, but long‐term outcomes can be severe, causing complete vision loss in about 60% of the patients. It is usually hospital‐acquired, and the source can be late‐onset empyema several months after cardiac surgery, in an immunocompromised patient. Systemic antibiotics should be supplemented with intravitreal agents with or without pars plana vitrectomy.